Rolling blackout is required for synaptic vesicle exocytosis. - Huang, F.D.; Woodruff, E.; Mohrmann, R.; Broadie, K. (Journal of Neuroscience, 2006)
Rolling blackout (RBO) is a putative transmembrane lipase required for phospholipase C-dependent phosphatidylinositol 4,5-bisphosphate-diacylglycerol signaling in Drosophila neurons. Conditional temperature-sensitive (TS) rbo mutants display complete, reversible paralysis within minutes, demonstrating that RBO is acutely required for movement. RBO protein is localized predominantly in presynaptic boutons at neuromuscular junction (NMJ) synapses and throughout central synaptic neuropil, and rbo TS mutants display a complete, reversible block of both central and peripheral synaptic transmission within minutes. This phenotype appears limited to adults, because larval NMJs do not manifest the acute blockade. Electron microscopy of adult rbo TS mutant boutons reveals an increase in total synaptic vesicle (SV) content, with a concomitant shrinkage of presynaptic bouton size and an accumulation of docked SVs at presynaptic active zones within minutes. Genetic tests reveal a synergistic interaction between rbo and syntaxin1A TS mutants, suggesting that RBO is required in the mechanism of N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE)-mediated SV exocytosis, or in a parallel pathway necessary for SV fusion. The rbo TS mutation does not detectably alter SNARE complex assembly, suggesting a downstream requirement in SV fusion. We conclude that RBO plays an essential role in neurotransmitter release, downstream of SV docking, likely mediating SV fusion.